Ectoparasite diversity in pets and livestock from Puducherry, India. Issue 7 (3rd October 2021) - Nataraj, Nikeshraj; Muthuraman, Krishnaraja; Ayyanar, Elango; Ashokkumar, Mathivanan; Kumar, Ashwani; Srinivasan, Lakshmy; Devaraju, Panneer
ABSTRACT: Ectoparasites in livestock and pets are associated with the transmission of diseases of veterinary and public health importance. The paucity of data on the ectoparasite diversity of pet and domestic animals in Puducherry is the basis for our study. Ectoparasites in animals brought to the veterinary dispensaries in Puducherry were retrieved and identified morphologically. Molecular confirmation of the ectoparasites was done by amplifying and sequencing the genes cytochrome oxidase I ( COI), 16s rRNA and 18s rRNA . A total of 792 animals were screened and 2625 ectoparasites were retrieved. The most common ectoparasite retrieved was ticks (n = 2140) followed by fleas (n = 326) and lice (n = 180). Eight tick species belonging to two genera were collected: Rhipicephalus sanguineus, Rh. simus, Rh. bursa, Rh. (Boophilus) annulatus, R. (Boophilus) microplus, Rh. haemaphysaloides, Haemaphysalis intermedia and Ha. bispinosa . Three sucking lice, Haematopinus quadripertusus, H. tuberculatus, Linognathus africanus, and two chewing lice, Heterodoxus spiniger and Trichodectes canis were found infesting the animals. Ctenocephalides felis felis was the only flea species observed to infest the animals. Common grazing areas and stray animals contributed to wide dispersal of the ectoparasites on different hosts. A longitudinal study might uncover the influence of season on ectoparasite prevalence and diversity in Puducherry.